2001
DOI: 10.1002/syn.1045
|View full text |Cite
|
Sign up to set email alerts
|

Effect of MPTP‐induced denervation on basal ganglia GABAB receptors: Correlation with dopamine concentrations and dopamine transporter

Abstract: We investigated the effect of MPTP-induced lesion of the substantia nigra pars compacta (SNpc) dopaminergic neurons on GABA(B) receptors in the basal ganglia of mice and monkeys using receptor autoradiography and in situ hybridization. The extent of the lesion was measured with striatal catecholamine content, striatal binding of (125)I-RTI-121 to dopamine transporter (DAT), and DAT expression in the SNpc. GABA(B) receptors in mice brain were evaluated using (3)H-CGP54626 and its expression was measured with ol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
28
1

Year Published

2002
2002
2012
2012

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 33 publications
(32 citation statements)
references
References 45 publications
3
28
1
Order By: Relevance
“…Given the fact that GABAergic neurons neither uptake nor respond to MPP ϩ , the only plausible mechanisms that could support a contribution to the observed gene dysregulation are circuit related or bystander. To the former point, previous work with an MPTP mouse model found a significant decrease in GABA B mRNA by ISH within the SN pars compacta (Calon et al, 2001). Because our array studies did not detect alteration in this transcript within either the MME or MML suggests the signal contribution and likely overall GABAergic neuronal contributions are quite small relative to the changes within the TH-positive population.…”
Section: Anatomical Pathological and Cell Type Considerationsmentioning
confidence: 52%
“…Given the fact that GABAergic neurons neither uptake nor respond to MPP ϩ , the only plausible mechanisms that could support a contribution to the observed gene dysregulation are circuit related or bystander. To the former point, previous work with an MPTP mouse model found a significant decrease in GABA B mRNA by ISH within the SN pars compacta (Calon et al, 2001). Because our array studies did not detect alteration in this transcript within either the MME or MML suggests the signal contribution and likely overall GABAergic neuronal contributions are quite small relative to the changes within the TH-positive population.…”
Section: Anatomical Pathological and Cell Type Considerationsmentioning
confidence: 52%
“…An unexpected observation made was the degree of [NAA] reduction seen in the SNpc indicated that secondary damage can occur to surrounding glutaminergic and GABAergic neurons (Calon et al, 1999(Calon et al, , 2001 All together, whether severely affected dopaminergic neurons can be protected from the ravages of PD-associated neurodegeneration using therapeutic strategies outlined in this study is not yet known. However, the data outlined in this report and by others support the idea that such a goal is achievable.…”
Section: Discussionmentioning
confidence: 88%
“…In patients and in the animal models of Parkinson's disease, GPe neurons have more burst firing than in normal conditions (Filion and Tremblay, 1991;Sterio et al, 1994;Nini et al, 1995;Beric et al, 1996;Boraud et al, 2001;Wichmann and Soares, 2006) that might effectively activate GABA B receptors at their innervation sites. The expression of GABA B receptors in the pallidum and STN was altered in parkinsonian subjects (Calon et al, 2001(Calon et al, , 2003; Johnston and Duty, (A-b). B, Another GPe neuron induced a similar slow inhibition to both single and burst stimulation (B-a).…”
Section: Discussionmentioning
confidence: 99%